1994
DOI: 10.1037/0893-164x.8.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Family history of smoking and young adult smoking behavior.

Abstract: This study compared the smoking behavior and smoking-related beliefs of young adult smokers who did and did not have a family history of cigarette smoking. Those with a family history of smoking smoked more cigarettes in a typical day, smoked for more years, perceived themselves as more addicted to cigarettes, had more positive beliefs about the psychological consequences of smoking, and reported stronger pleasurable relaxation motives and stimulation motives for smoking compared with their peers who had no fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
1
9
0
1
Order By: Relevance
“…Because the studies reviewed were not designed specifically to examine familial aggregation of smoking, it is not surprising that few studies met the methodological standards—and no one study met all of the methodological standards—required for systematic evaluation of familial aggregation in genetic epidemiology (but see Boomsma et al . 1994; Chassin et al . 1994 for approximations).…”
Section: Methodological Review Of Existing Studies On Familial Tobaccmentioning
confidence: 99%
“…Because the studies reviewed were not designed specifically to examine familial aggregation of smoking, it is not surprising that few studies met the methodological standards—and no one study met all of the methodological standards—required for systematic evaluation of familial aggregation in genetic epidemiology (but see Boomsma et al . 1994; Chassin et al . 1994 for approximations).…”
Section: Methodological Review Of Existing Studies On Familial Tobaccmentioning
confidence: 99%
“…Covariates included in the model were gender (female as the reference group), ethnicity (White as the reference group), BMI category (overweight as the reference group), weight loss goals (no goals as the reference group), perceptions of peer smoking prevalence (most/all as the reference group), and parental smoking behaviors (either parent smokes as the reference group). These covariates were selected based on prior research that has indicated the importance of these factors on youth tobacco experimentation and use (Chassin et al, 1994;Flay et al, 1998;Klesges, Robinson, & Zbikowski, 1998;Simons-Morton et al, 1999). Controlling for all other variables, smoking status was regressed on the two attitudinal measures of interest (each entered as continuous variables); odds ratios and confidence intervals were examined to determine the likelihood of participants being in each smoking category based on attitudes.…”
Section: Independent Variablesmentioning
confidence: 99%
“…For example, a large body of theoretical and empirical evidence highlights the importance of examining related attitudes when seeking to better understand youth smoking (e.g., Ayatollahi, Mohammadpoorasl, & Rajaeifard, 2005) and intentions to smoke (e.g., Smith, Bean, Mitchell, Speizer, & Fries, 2006). Other psychosocial factors, such as peer and parental smoking attitudes and behaviors, have also been found to be associated with adolescent smoking (Bricker et al, 2006;Chassin, Presson, Sherman, & Mulvenon, 1994;Flay, Hu, & Richardson, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous studies have demonstrated that individuals with histories of cigarette smoking in first-degree relatives are at particular risk of persistent smoking compared to those without such histories (Heath & Martin 1993;Chassin et al 1994Chassin et al ,1996Kendler et al 1999). Shared environmental influences, along with genetic factors, have been emphasized as important contributors to persistent smoking (Heath & Martin 1993;Kendler et al 1999).…”
Section: Introductionmentioning
confidence: 99%